Distribution of Periphyton in the Upstream Section of Citarum River, West Java, Indonesia - Noviana, Isma; Pribadi, Tri Dewi Kusuma Ningrum; Rosada, Keukeu Kaniawati (Jurnal Biodjati, 2020)
PeriphytonÂ indeedÂ playsÂ anÂ undeniably vitalÂ role as primary producers in the food web within aquatic ecosystems such as rivers. The existence of periphyton will affect the populations of the aquatic organisms at higher trophic level, thusÂ it isÂ interesting to be explored, especially in big riversÂ like Citarum. This study aimed to explore the distribution of periphyton, includingÂ itsÂ types and abundance at several stations in the upstreamÂ part of CitarumÂ RiverÂ based onÂ theÂ land use in the riverbanks, in the dry season of 2018. Samples were taken at nine stations, namely Gunung Wayang Springs, Outlet Cisanti atÂ the valley of MountÂ Wayang, and theÂ connectingÂ tributariesÂ as follows: Cihejo, Cibuni, Cirasea, Cikaro, Cisangkuy, Cikapundung, and Ciwidey. Samples of periphyton were taken from the substrate of stone, wood, plastic,Â and macrophytes at three sampling points of each station. Periphyton samplesÂ were thenÂ scraped off from the surface of the substrate, where the depositÂ would then be filtered using plankton net No.20, preserved with Lugol 1% and subsequently identified. The results showed there were 83 species from 58 genera of both phytoperiphyton and zooperiphyton, classified as periphytonÂ found on the sites. The total abundance of phytoperiphyton ranged between 2.3 x 104 ind/m2Â and 1.3 x 108Â ind/m2Â where the total abundance of zooperiphyton covered from 4.7 x 102Â ind/m2Â to 3.7 x 105Â ind/m2. The highest and the lowest numbers of total abundance of periphyton were shown at stations of Gunung Wayang Spring and Cirasea tributary, respectively.Â